Fricative productions of Mandarin-speaking children with cerebral palsy: the case of five-year-olds. (3rd March 2020) - Liu, Chin-Ting; Chen, Li-Mei; Lin, Yu-Ching; Cheng, Ching-Yi; Lin, Yung-Chieh
ABSTRACT: This study aimed at improving the understanding of speech characteristics of fricatives produced by five-year-old Mandarin-acquiring children with cerebral palsy (CP). Productions from nine CP children and nine gender-and-age-matched typically developing (TD) children were collected and analyzed. Results from transcription indicated that the CP group had lower production accuracy rates for all the five fricatives in Mandarin Chinese. Additionally, when the CP children failed to articulate the target fricative segments, they tended to delete them or convert them into non-continuant segments. Results from acoustic analyses indicated that the M2 values of the labiodental [f] and the M1 and M2 values of the alveolar [s] were higher among the CP children. The experimental results revealed that: (1) Observable differences were available once the age of the groups was properly controlled and acoustical measurements were adopted; (2) the lack of finer-grained speech motor control abilities among CP children were reflected in the M1 and M2 values; (3) for segments at the anterior places, the clinical group failed to extend the articulatory gestures to the desirable positions. It is suggested that future studies focusing on different age groups and children with different native languages would help to approach the nature of articulatory barriers among individuals with CP.